2022
DOI: 10.3390/microorganisms11010057
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Associated with the Roots of Common Bean (Phaseolus vulgaris L.) at Different Development Stages: Diversity and Plant Growth Promotion

Abstract: Current agricultural methodologies are vulnerable to erratic climate and are dependent on cost-intensive fertilization to ensure high yields. Sustainable practices should be pursued to ensure food security. Phaseolus vulgaris L. is one of the most produced legumes worldwide and may be an alternative to reduce the environmental impact of meat production as a reliable source of high-quality protein. Plant growth-promoting rhizobacteria (PGPR) are emerging as a sustainable option to increase agricultural producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…To the best of our knowledge, these genera have also been found in different high-throughput studies but not in the microbiome of Phaseolus vulgaris (23). However, Rocha et al (63) recently reported a plethora of cultivated PGPR in the rhizosphere of Phaseolus vulgaris L., variety “Patareco,” in agreement with the metagenomic PGPR registered in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To the best of our knowledge, these genera have also been found in different high-throughput studies but not in the microbiome of Phaseolus vulgaris (23). However, Rocha et al (63) recently reported a plethora of cultivated PGPR in the rhizosphere of Phaseolus vulgaris L., variety “Patareco,” in agreement with the metagenomic PGPR registered in this study.…”
Section: Discussionsupporting
confidence: 90%
“…In the rhizosphere of the Pinto Saltillo cultivar, abundance at the genus level indicated that a group of Promoter-Growth Plant Rhizobacteria plays an important role (63). Consistently, the genera Pseudomonas , Rhizobium , Pantoea , and Variovorax were the most abundant in the rhizosphere of the cultivar Pinto Saltillo.…”
Section: Discussionmentioning
confidence: 99%